KONVERSI SISTEM ABSENSI KARYAWAN PADA SEKOLAH TINGGI MANAJEMEN INFORMATIKA (STMIK) ASIA - Sidi, Agus Purnomo (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2016)
The uses of technology in daily organization operational becomes ordinary thing. The optimum technology uses are the use technology thatÂ  align with the need of the users in order gaining efficiency and inclining productivity. STMIKÂ  Asia has used finger print absensce media for recording its employees attendence.Yet, the attendence machine that has been used for a long period, can not accomodate the Human Resource DepartmentâsÂ  need in order to observe its employee presence during working-hours.The emergence information regarding the employee presence during working hours, is supported by manual written absence book.However, this manual written book, can not provide a real-time information the presence of the employee. Furthermore, in the end of the period, recapitulation absence book become a burden, take a lot of time for inputting data to the computer. Thus, STMIK Asia adopting other technology in order to fulfill the need of Human Resource Department. The new adapted technology is not a more modern or sophisticatedÂ  machine, however the new technology accomodates employees attendence system that align with STMIK Asia needs.Â Keywords: attendence, finger print, convertion, HR Information System